Analisa Faktor-Faktor yang Mempengaruhi Use Behavior Mahasiswa Berbelanja di Media Sosial dengan Behavior Intention sebagai Mediasi - Nurjanah, Listia; Rusyen, Karina; Lady, Lady (Universitas Batanghari Jambi, 2025)
This study is a quantitative study that discusses the factors that influence the use of social commerce by students in Batam City. Through Google Form, 275 questionnaires have been collected from respondents. The results of the study indicate that the behavioral intention variable is able to mediate the influence of the performance expectancy, effort expectancy, social influence, facilitating condition variables on the use behavior variable of students in Batam City. The behavioral intention variable is not able to mediate the influence of the price value variable on the use behavior variable, but the behavioral intention variable has a positive and significant effect on the use behavior of students in Batam City.